Libri di e per Religiose: Ferrara XV secolo - Toniolo, Federica (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
This paper examines illuminated manuscripts produced by or linked to important female religious houses in Ferrara and the Este territories, to argue for the strong rapport between court and monastic or conventual patronage, especially during the reigns of Borso d'Este and Ercole I (1450-1505). A central role was played by sisters of the convent of the Clarissan Franciscans of Corpus Domini in Ferrara, where Caterina Vigri, a scribe and later founder of Corpus Domini in Bologna, lived. Other important centers included the Benedictine Monastery of Sant'Antonio in Polesine, and the Convent of Santa Caterina (Dominican Tertiaries), founded by Lucia Broccadelli da Narni, counselor to Duke Ercole. The surviving manuscripts allow for examination of how their images and texts reflect the devotional intensity promoted in these religious houses. A new analysis of well-known manuscripts will be joined by the presentation of a previously unstudied Rule of Saint Augustine for a female congregation painted in Ferrarese style, whose origin is still unknown.